2020
DOI: 10.1038/s41390-020-1065-5
|View full text |Cite
|
Sign up to set email alerts
|

A literature review of 2019 novel coronavirus (SARS-CoV2) infection in neonates and children

Abstract: A literature review of 2019 novel coronavirus (SARS-CoV2) infection in neonates and children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
74
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 96 publications
2
74
0
1
Order By: Relevance
“…However, nothing similar to was observed in our patient is described [1][2][3]. Neurological manifestations have been observed in adults with COVID-19 that could play a role in the respiratory failure of these patients [6].…”
Section: A C C E P T E Dsupporting
confidence: 79%
See 2 more Smart Citations
“…However, nothing similar to was observed in our patient is described [1][2][3]. Neurological manifestations have been observed in adults with COVID-19 that could play a role in the respiratory failure of these patients [6].…”
Section: A C C E P T E Dsupporting
confidence: 79%
“…Few data are available for SARS-CoV-2 infection in neonates and the clinical pictures described in literature are mainly respiratory or gastrointestinal disease associated with fever [1][2][3], with rare neurological manifestations, including lethargy reported also in neonates.…”
Section: A C C E P T E Dmentioning
confidence: 99%
See 1 more Smart Citation
“…This virus originated in the city of Wuhan, Hubei Province, China, in late 2019 and quickly spread throughout Europe, the United States of America, and other Latin American countries. 1 In March 2020, the World Health Organization (WHO) declared a pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Public health interventions, such as school closures, have been shown to decrease the risk of community viral spread on a population level. 9 Epidemiologists have found that although Original Research children are less likely to exhibit SARS-CoV-2 symptoms compared with adults, 10,11 they also have more subtle presentations 11e13 and may spread disease to family members at home. 14, 15 On an individual level, these data suggest that families with children at home, particularly families who are not able to physically distance, may be at a higher risk of SARS-CoV-2 acquisition.…”
Section: Introductionmentioning
confidence: 99%